Autosomal‐dominant myopia associated to a novel P4HA2 missense variant and defective collagen hydroxylation. Issue 5 (5th March 2018) - Napolitano, F.; Di Iorio, V.; Testa, F.; Tirozzi, A.; Reccia, M.G.; Lombardi, L.; Farina, O.; Simonelli, F.; Gianfrancesco, F.; Di Iorio, G.; Melone, M.A.B.; Esposito, T.; et al.
Abstract : We recently described a complex multisystem syndrome in which mild‐moderate myopia segregated as an independent trait. A plethora of genes has been related to sporadic and familial myopia. More recently, in Chinese patients severe myopia (MYP25, OMIM:617238) has been linked to mutations in P4HA2 gene. Seven family members complaining of reduced distance vision especially at dusk underwent complete ophthalmological examination. Whole‐exome sequencing was performed to identify the gene responsible for myopia in the pedigree. Moderate myopia was diagnosed in the family which was associated to the novel missense variant c.1147A > G p.(Lys383Glu) in the prolyl 4‐hydroxylase, alpha‐polypeptide 2 ( P4HA2 ) gene, which catalyzes the formation of 4‐hydroxyproline residues in the collagen strands. In vitro studies demonstrated P4HA2 mRNA and protein reduced expression level as well as decreased collagen hydroxylation and deposition in mutated fibroblast primary cultures compared to healthy cell lines. This study suggests that P4HA2 mutations may lead to myopic axial elongation of eyeball as a consequence of quantitative and structural alterations of collagen. This is the first confirmatory study which associates a novel dominant missense variant in P4HA2 with myopia in Caucasian patients. Further studies in larger cohorts are advisable to fully clarify genotype‐phenotype correlations. Abstract :